THE DISCIPLINE OF HISTORY UNDER A NEW VIEW IN THE INSERTION OF TECHNOLOGY IN EDUCATION - Bezerra Cavalcanti, Genivaldo (Revista Gênero e Interdisciplinaridade, 2025)
The integration of technology in the teaching of History has the potential to make learning more dynamic and interactive. However, its full adoption in the classroom faces several challenges. The main obstacles aren’t just a lack of interest, but also include teachers’ insufficient technical knowledge and inadequate training. Furthermore, a deficient school infrastructure (computers, internet, etc.), the difficulty in curating quality online content, and the need to rethink teaching methodologies are significant barriers. The heavy workload of teachers is also cited as a factor that limits innovation. Despite these challenges, the use of digital tools in teaching History can bring several benefits, such as increased student motivation and autonomy, improved teaching quality, and the encouragement of critical thinking. Technology allows students to move from being mere spectators to becoming producers of knowledge. For this transformation to happen, the text concludes that a joint effort is needed, combining investment in infrastructure, continuous training for teachers, and the development of specific, high-quality educational resources. The main goal is for technology to serve as a powerful ally for a more modern, engaging, and relevant way of teaching History.